Correction: The value of universally available raw NMR data for transparency, reproducibility, and integrity in natural product research. Issue 1 (23rd November 2018) - McAlpine, James B.; Chen, Shao-Nong; Kutateladze, Andrei; MacMillan, John B.; Appendino, Giovanni; Barison, Andersson; Beniddir, Mehdi A.; Biavatti, Maique W.; Bluml, Stefan; Boufridi, Asmaa; Butler, Mark S.; Capon, Robert J.; et al.
Abstract : Correction for 'The value of universally available raw NMR data for transparency, reproducibility, and integrity in natural product research' by James B. McAlpine et al., Nat. Prod. Rep., 2018, DOI: ;10.1039/c7np00064b .